Development of space time block code using QPSK and GMSK modulation technique / Amer Masri Roslan - Roslan, Amer Masri (2006)
This thesis will deal with two transmit antenna (also known diversity technique) and one receive antenna. And appropriate to space-time block code (STBC) technique against the Rayleigh fading channel by using QPSK and GMSK modulation techniques. As will be shown, the performance of diversity system depends on the combining scheme in order to choose the higher SNR and lower noise. The design of STBC is to achieve full spatial diversity against fading channel. At the transmitter, information signal are divide into two signals, after that these signals are encode by cyclic code, then modulated into the analogue carrier frequency using GMSK or QPSK. At the receiver, the signals are selected by using selective method by looking which signal has a higher SNR, lower noise then demodulated and decode back to produce the'message. Finally, comparison will be made, which modulation techniques will give greatest result in diversity scheme and to prove that diversity better than no diversity base on bit error rate (BER). This project use MATLAB version 7.1 to simulate the performance of STBC.